2019
DOI: 10.3982/ecta14673
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Truth‐Telling

Abstract: Private information is at the heart of many economic activities. For decades, economists have assumed that individuals are willing to misreport private information if this maximizes their material payoff. We combine data from 90 experimental studies in economics, psychology, and sociology, and show that, in fact, people lie surprisingly little. We then formalize a wide range of potential explanations for the observed behavior, identify testable predictions that can distinguish between the models, and conduct n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

61
503
13

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 620 publications
(633 citation statements)
references
References 125 publications
61
503
13
Order By: Relevance
“…As a robustness check, it was found that magnitude of cheating in the first phase of the study was a good predictor of propensity for further cheating in the second phase (which employed a different task). Note that this behavior has nothing to do with the moral cleansing reported in earlier studies and is contrary to a study of Abeler et al (in press) showing that the lying behavior of adults under a roll a die paradigm does not change if they make several repeated reports.…”
Section: Discussioncontrasting
confidence: 99%
“…As a robustness check, it was found that magnitude of cheating in the first phase of the study was a good predictor of propensity for further cheating in the second phase (which employed a different task). Note that this behavior has nothing to do with the moral cleansing reported in earlier studies and is contrary to a study of Abeler et al (in press) showing that the lying behavior of adults under a roll a die paradigm does not change if they make several repeated reports.…”
Section: Discussioncontrasting
confidence: 99%
“… The gender effect is in line with previous studies that find that women are less likely to lie in economic experiments (Dreber and Johannesson, ; Abeler et al ., ) as well as with the finding that verification of personal data decreases males’ (but not females’) measured willingness to share personal data (Schudy and Utikal, ). The Preferences data are not verifiable and, according to the above‐mentioned studies, are more likely to be reported truthfully for women.…”
mentioning
confidence: 79%
“…That said, we note that analyzing each distribution separately revealed no significant difference between the observed distribution and the expected distribution of “choosing the highest of three rolls” in two out of the three conditions. Recent research shows that people use the “highest of three” strategy across different countries (Gächter & Schulz, ), and that being instructed to test the die (and thus observe additional die roll outcomes) increases cheating behavior compared with participants who are not instructed to test the die (Abeler, Nosenzo, & Raymond, ). We encourage future research to use meta‐analytical approaches to assess the extent to which this strategy is robust to different settings.…”
Section: Discussionmentioning
confidence: 99%